Protokol Pemulasaran Jenazah Akibat Covid-19 Berdasarkan Fatwa MUI No. 18 Tahun 2022 - Azzahra Sabrina Hanifa; Adede Dicky Ardian; Yaniz Naura Naviana Haryadi (MASADIR: Jurnal Hukum Islam, 2022)
This article aims to provide an explanation of the law regarding the handling of corpses infected with Covid-19 (an analysis study of the MUI Fatwa Number 18 of 2020). The main problem in this research is what is the MUI's view of the law regarding the management of the bodies of Covid-19 victims? What is the analysis of MUI Fatwa Number 18 of 2020 regarding the protocol for treating bodies infected with Covid-19? The type of research used in this research is qualitative research (descriptive qualitative). The data source used is library research. The approach used is a normative approach, namely legal research conducted by examining literature review materials or secondary data as the main material for research by conducting a search of various regulations related to the problem to be studied. The data collection method used is by reviewing manuscripts and studying literature. The data collected mainly comes from books that are primary, then followed by supporting books that are secondary and as a complement, the researcher also uses tertiary data in providing an explanation of primary and secondary data. The data processing method is by reviewing, checking and interpreting the collected data so that the phenomenon being studied can be described. Furthermore, for the data analysis method, the researcher used a descriptive qualitative method, namely analyzing data which was carried out by presenting various data from the results regarding the process of handling the bodies of Covid-19 according to the MUI Fatwa. The results of the research are from the researcher's analysis to answer the problem of how the protocol for treating corpses due to Covid-19 is based on the MUI Fatwa Number 18 of 2020, in accordance with the results of the MUI Fatwa study Number 18 of 2020, in the view of sharia, Muslims who died due to the Covid-19 outbreak are included the category of martyrs in the afterlife and the rights of the corpse must be fulfilled, including washing, shrouding, offering prayers, and burial, where the implementation must maintain the safety of officers by complying with medical protocol provisions. Keywords: Restoration Protocol, Dead Body of Covid-19, MUI Fatwa No. 18 of 2020